2020
DOI: 10.1111/ijfs.14765
|View full text |Cite
|
Sign up to set email alerts
|

Textural and physicochemical predictors of sensory texture and sweetness of boiled plantain

Abstract: Prediction of firmness by puncture force for boiled plantain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Given that the crumbly samples were also easy to break their prediction by PF could 10970010, ja, Downloaded from https://onlinelibrary.wiley.com/doi/10.1002/jsfa.12589 by CIRAD -DGDRS -DIST, Wiley Online Library on [14/04/2023]. See the Terms and Conditions (https://onlinelibrary.wiley.com/terms-and-conditions) on Wiley Online Library for rules of use; OA articles are governed by the applicable Creative Commons License be due to co-linearity between these sensory traits, as reported by Kouassi et al 6 for boiled plantain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that the crumbly samples were also easy to break their prediction by PF could 10970010, ja, Downloaded from https://onlinelibrary.wiley.com/doi/10.1002/jsfa.12589 by CIRAD -DGDRS -DIST, Wiley Online Library on [14/04/2023]. See the Terms and Conditions (https://onlinelibrary.wiley.com/terms-and-conditions) on Wiley Online Library for rules of use; OA articles are governed by the applicable Creative Commons License be due to co-linearity between these sensory traits, as reported by Kouassi et al 6 for boiled plantain.…”
Section: Discussionmentioning
confidence: 99%
“…Kouassi et al 6 reported that an increase in the soluble solid content of 4°Brix was sufficient for the panellists to perceive a significant and coherent difference. This led to a 2-point increase in the sweetness of boiled plantain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 A. The sweetness substantially increased from RS4 to RS7, indicating that starch hydrolyzed to produce soluble solids during this period, which increased the sugar content of banana ( Kouassi et al, 2020 ). Notably, there was no obvious change in sweetness after RS7.…”
Section: Resultsmentioning
confidence: 99%